A hoatzin fossil from the middle Miocene of Kenya documents the past occurrence of modern-type Opisthocomiformes in Africa. (15th January 2014) - Mayr, Gerald
Abstract: The fossil bird Namibiavis senutae from the early Miocene of Namibia was recently identified as an African stem-group representative of Opisthocomiformes (hoatzins). The species is known only from two wing and pectoral girdle bones, however, and the extent to which African Opisthocomiformes resembled their Neotropical relatives in skeletal morphology has remained elusive. I report a hoatzin tarsometatarsus from the middle Miocene of Maboko Island in Kenya, which, except for a peculiar autapomorphic fusion of the first metatarsal, closely matches the tarsometatarsus of the extant Opisthocomus hoazin . Although a well-founded classification on the species level is not possible, the new fossil documents the existence of essentially modern-type Opisthocomiformes in the Miocene of Africa. Being 2–2.5 Ma younger than N. senutae, the specimen further extends the temporal and spatial range of Miocene African Opisthocomiformes.